2009
DOI: 10.1007/s00127-009-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to people with mental disorders: a mental health literacy survey in a rural area of Maharashtra, India

Abstract: Introduction People with mental disorders experience discrimination as a consequence of stigmatising attitudes that are largely socio-culturally constructed. Thus, there is a need to understand local contexts in order to develop effective programs to change such attitudes. We undertook a mental health literacy survey in rural Maharashtra, India, prior to developing a mental health training program for village health workers (VHWs) in a primary health care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 34 publications
12
98
3
Order By: Relevance
“…The responses to specific items in the survey of attitudes, moreover, were consistent with those beliefs: 50.6% of students said they would not be frightened if approached by someone with a mental illness, disagreed that people with a mental illness should be avoided. Such results which are different from those reported in some previous studies (Kermode et al, 2009;Chong et al, 2007;Hugo et al, 2003), suggest the possibility that the youths of today have not picked up the same fears of mental illness that persist among general populations.…”
Section: Discussioncontrasting
confidence: 92%
“…The responses to specific items in the survey of attitudes, moreover, were consistent with those beliefs: 50.6% of students said they would not be frightened if approached by someone with a mental illness, disagreed that people with a mental illness should be avoided. Such results which are different from those reported in some previous studies (Kermode et al, 2009;Chong et al, 2007;Hugo et al, 2003), suggest the possibility that the youths of today have not picked up the same fears of mental illness that persist among general populations.…”
Section: Discussioncontrasting
confidence: 92%
“…Commenting on developing nations in Asia, Lauber and Rossler (2006) noted that stigmatization is more prevalent in these cultures than in Western cultures (47). Kermode et al (2009) found that the majority of participants from his study in rural Maharashtra did not conceptualise depression or psychosis as a "real medical issue" (38) . Instead, they attributed causation to social and economic factors, which the authors suggested may be appropriate given the prevalence of poverty as well as gender-and caste-based discrimination in the region.…”
Section: Predictors Of Depressionmentioning
confidence: 99%
“…As a result, Indian participants may not have recognised the SMFQ items as mental health items and it is possible that they may have provided responses that were less influenced by social stigma. For example, studies have demonstrated that stigma acts as a widespread cultural barrier to the reporting of symptoms of mental health in developing nations in Asia, including a recent study conducted in Maharashtra, the state where Mumbai is located (38). Self-critical depressive features emerged as a major cross-cultural difference.…”
Section: Differences In Levels Of Symptomsmentioning
confidence: 99%
“…A range of issues may assist with social inclusion of individuals affected by severe mental illness in the third world. It has been noticed that cultural mechanisms may be more accepting of mental illness in these countries (Kermode et al 2009, Postert 2010. However, Rahman & Prince (2008) note that there is a significant amount of stigma experienced by families of people affected by severe mental illness in third world countries.…”
Section: Social Inclusionmentioning
confidence: 99%